Design of energy-efficient multiplier based on 3:2 compressor - Hussain, Inamul; Chaudhury, Saurabh (Institute of Advanced Engineering and Science, 2021)
A multiplier circuit is one of the most important functional blocks of many nano-electronic, control and automation applications. In this work, an energy-efficient multiplier is reported based on a 3:2 compressor. The multiplier has been designed in three different parts. In the first part, a partial product (PP) generator is used. In the second part, the partial products are reduced which is termed as PPP (partial product processing). Whereas in the third step final addition is performed. PPs are produced by using AND gates. The PPP is designed in two-phase. In the first phase, the Wallace tree logarithm has been used to reduce the PPs. Whereas, in the second phase the PPs are reduced by using energy-efficient half adder and 3:2 compressor. At last, in the third step, by using a carry-save adder final addition has been computed. The performance analysis of the designed multiplier is evaluated and compared with other multiplier circuits. The multiplier shows performance improvements by 20.55%-46% for the power supply variation from 1.2 V to 0.6 V. All the simulations and analyses have been carried out by using the Synopsys EDA tool.